EDUKASI PERAWATAN LUKA PASIEN HEMIPARESIS POST-OP KRANIOTOMI UNTUK MENCEGAH TEKANAN, TRAUMA, DAN PERSONAL HYGIENE PADA KELUARGA PASIEN DI RUANG OK RSUP DR. TADJUDDIN CHALID - Elva Vadila; Suhermi; Idelriani; Erna Marini (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Post-craniotomy wound care education plays a crucial role in preventing complications such as pressure injuries, recurrent trauma, and infection caused by inadequate personal hygiene, particularly in hemiparesis patients who experience limited mobility. This case study aims to evaluate the effectiveness of postoperative education in improving the patient’s family knowledge regarding wound care after craniotomy at the Operating Room of Dr. Tadjuddin Chalid General Hospital. Pre Experimental Design through One Group Pre-Post Test. The pre-test results showed a score of 60%, with errors related to the use of support pillows for pressure prevention and the importance of scalp and hair hygiene in infection control. After receiving education through lectures, demonstrations, and interactive discussions, the participant’s post-test score increased to 100%, indicating complete comprehension of the material. The 40% increase met the criteria for significant improvement and was supported by the participant’s ability to accurately recall the main educational points.  Evaluation also revealed positive behavioral changes, where the patient’s family demonstrated improved understanding and the ability to perform appropriate wound care, recognize risk areas, and implement proper personal hygiene measures. These findings confirm that postoperative educational interventions effectively enhance knowledge and readiness among families caring for hemiparesis patients after craniotomy. This intervention supports recovery, prevents complications, and improves the quality of perioperative nursing care.